Zero waste counseling in the bikesah program as an intervention in waste management problems - Fitri, Nour; Wahyunikmaturohmah, Wahyunikmaturohmah; Angraini S, Dista (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Waste management by burning is still a problem that is often found in the community. Counseling on zero waste waste management is one of the solution efforts to reduce the volume of waste disposed of in landfills. Objective : The BIKESAH program aims to increase awareness of SMPN 2 PPU students about the importance of proper waste management at school and to minimize the use of disposable drinking bottles by bringing drinking water tumblers to school. Research Methods/ Implementation Methods : he activity method is carried out in three stages, including the preparation stage, the implementation stage, and the final stage, namely monitoring and evaluation. The BIKESAH program was attended by 19 participants who were students of SMPN 2 PPU. Results : The BIKESAH program successfully increased participants' knowledge by 6% about zero waste management, as seen from the results of the Pre-Test and Post-Test. Followed by 19 students of SMPN 2 PPU, this program showed high enthusiasm during discussions. Participants became more aware of the importance of proper waste management and began to apply the principle of zero waste, such as bringing tumblers to school to reduce the use of disposable bottles. It is hoped that this program will encourage changes in participants' behavior in protecting the environment. Conclusion/Lesson Learned : The implementation of the BIKESAH program went well, with participants enthusiastic in the discussion. The increase in knowledge was recorded at 6% from the pretest and posttest, it is expected that participants can apply zero waste practices in the school environment.